Environmentalism in the Face of the Ecological Crisis. - Vargas Campos, Ronulfo (2023)
The article emphasizes the importance of environmentalism for an adequate understanding of the ecological crisis at all levels. To this effect, it analyzes the origins of environmentalism, its diverse theoretical expressions and its relation with ecology and the dimensions of human action that potentiate an environmental crisis: politics, economy and the culture of overproduction and mercantile overconsumption, which is promoted by the economic system. The understanding of the ecological crisis from the perspective of environmentalism is key to satisfy the imperative of survival to which the imperative of the good life is subordinated.